Pengaruh stres kronis terhadap kesehatan mental dan fisik pada remaja - Iriyanto, Shilham Adzin Adani (Maliki Interdisciplinary Journal, 2024)
Chronic stress is a condition that occurs when a person experiences continuous pressure without time to recover. In adolescents, chronic stress can be caused by various factors such as academic pressure, family problems, and social dynamics. This study aims to examine the effect of chronic stress on the mental and physical health of adolescents. The findings show that chronic stress has a significant impact on increasing the risk of mental disorders such as depression and anxiety, as well as physical disorders such as hypertension and sleep disorders. Appropriate interventions are needed to reduce the negative impact of chronic stress on adolescents.